The Influence of Facilities and Service Quality on Visitor Satisfaction at the 2024 Purnama Bersantai Music Concert - Anhar, Aidil; Parlindungan, Anggiat (CV. Civiliza Publishing, 2025)
The music concert industry in Indonesia continues to experience significant growth, particularly in the city of Medan, which has begun actively developing various local and national-scale entertainment events. One concert that attracted public attention was